1995
DOI: 10.1111/j.1528-1157.1995.tb00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Language Before and After Temporal Lobectomy: Specificity of Acute Changes and Relation to Early Risk Factors

Abstract: We evaluated language functions in 154 patients with left hemisphere speech dominance undergoing anterior temporal lobectomy (ATL). Measures of phonemic and semantic fluency, confrontation naming, repetition, comprehension, and reading were administered before and 3 weeks postoperatively. Patients were grouped by focus (left, LT; right, RT) and presence of early risk factors for development of seizures (ER, early risk, < or = 5 years; NER, no early risk): (LT-ER, n = 45; RT-ER, n = 49; LT-NER, n = 27; RT-NER, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
82
1
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 22 publications
14
82
1
4
Order By: Relevance
“…These percentages indicate that standard ATL as assessed by other than nominal speech measures, is a safe procedure with regard to language outcome. Our findings replicate those of Saykin et al (10): As shown on a battery of language tests, only nominal speech of the patients was affected. Saykin et al (10) assessed patients acutely, and our current findings suggest that the same trend they reported persists 6-8 months postoperatively.…”
Section: Evaluation Of Nominal Speech Decline Risk For the Individualsupporting
confidence: 81%
See 2 more Smart Citations
“…These percentages indicate that standard ATL as assessed by other than nominal speech measures, is a safe procedure with regard to language outcome. Our findings replicate those of Saykin et al (10): As shown on a battery of language tests, only nominal speech of the patients was affected. Saykin et al (10) assessed patients acutely, and our current findings suggest that the same trend they reported persists 6-8 months postoperatively.…”
Section: Evaluation Of Nominal Speech Decline Risk For the Individualsupporting
confidence: 81%
“…Our findings replicate those of Saykin et al (10): As shown on a battery of language tests, only nominal speech of the patients was affected. Saykin et al (10) assessed patients acutely, and our current findings suggest that the same trend they reported persists 6-8 months postoperatively. The degree to which nominal speech declines, when it does, and the degree to which it subsequently returns to preoperative levels, remains to be determined and is an important issue.…”
Section: Evaluation Of Nominal Speech Decline Risk For the Individualsupporting
confidence: 81%
See 1 more Smart Citation
“…Ultimately, assessing both pre-and post-operative performance in the same patients is necessary to definitively attribute such deficits to the impact of resective surgery. If such a study were to be performed, it would be helpful to evaluate potential intervening variables that might impact outcome on these category-specific measures (e.g., age of seizure onset, early risk factors for epilepsy, impact of primary pathologies leading to epilepsy), as these factors have proven to impact performance outcome using standard naming measures (Davies, Risse, & Gates, 2005;Saykin et al, 1995;Yucus & Tranel, in press) Although some of the newer antiepileptic drugs (AEDs) appear to negatively impact language functioning (e.g., topiramate, zonisamide: Kockelmann, Elger, & Helmstaedter, 2003;L. M. Ojemann et al, 2001), this finding has primarily involved verbal fluency rather than confrontation naming.…”
Section: Discussionmentioning
confidence: 99%
“…Memory risk is greatest following resection of the language dominant temporal lobe, and when the diseased temporal lobe to be resected still actively contributes to memory formation (i.e., high functional adequacy; Chelune, 1995). The risk of naming decline following left ATL is also well-established (Bell et al, 2000;Langfitt & Rausch, 1996;Saykin et al, 1995;Schwarz et al, 2005), and the role of the hippocampus in naming performance both pre-and postoperatively is increasingly appreciated (Hamberger et al, 2007;Seidenberg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%